Proses Penyelesaian Perkara Pembatalan Perkawinan Sepersusuan Dan Akibat Hukum Terhadap Anak Yang Dilahirkan (Analisis Putusan Pengadilan Agama Surakarta) - Nurhuda, Nova Cumala Amina, Nuswardhani, S.H., S.U (2017)
This study aims to determine the settlement process of marriage annulment sibling, knowing consideration of evidence and the judge in determining the verdict on marriage annulment cases sibling as well as to determine the legal consequences arising after the decision of sibling marriage and to determine the legal status of children who are born. The method used by the authors is that which examines the normative law based on the rule of law and the principle in law. This is a descriptive study. This study describes the systematic and comprehensive on sibling marriages that have occurred and the legal effects of child birth. The results showed that the process of sibling marriage annulment filed by parties who feel disadvantaged then examined the trial to determine the facts that have occurred then the judge handed down the verdict. Consideration of evidence and the judge in determining the verdict on marriage annulment case the sibling is by examining the evidence submitted by the applicant and the defendant both written evidence and witness evidence. The legal consequences arising after the decision of sibling marriage was against the marriage party was canceled is not allowed to be reconciled. While setatus law against child born is to remain as a legitimate child in accordance with Article 28 paragraph (2) Marriage Law that the decision is not retroactive to the children born of the marriage.